EFEKTIVITAS LAYANAN FOTOKOPI SEBAGAI PENGGANTI PEMINJAMAN KOLEKSI BAGI PEMUSTAKA LUAR UPT PERPUSTAKAAN UNTAN - Anjarwati, Eka Putri; Madeten, Sisilya Saman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Abstract The main problem in this final task is that there are still outside leaders who do not know not allowed to borrow collections but can only photocopy and read on the spot. The purpose of this study is to find out the effectiveness of photocopying services as a substitute for collectible lending for UPT Untan library. The type of research used is descriptive research with a quantitative approach. The respondents numbered 17 people from various students of Universities / Institutes / Higher Schools in Pontianak and some even came from universities outside West Kalimantan. The data was collected using a questionnaire in the form of a Google Document link distributed through WhatsApp. Based on the results of data analysis using SPSS version 18 showed that the results of the questionnaire validity test were declared valid because it exceeded the signification level r calculated greater than the r table and with reliability test results declared reliable because 0.905 0.60. While the results of the calculation of the effectiveness of the service using the percentage of interpretation of the score based on intervals obtained the number 72.5% which means effective. Keywords : Effectiveness, Photocopying Services, Outside Library